Functions of Relationship Capital in Rural Public Sports Service - Zhu, Wanjing (Asian agricultural research, 2014)
The field survey of two natural villages found that the relationship capital plays an important role in rural public sports service benefiting from the rural elite operation mode. However,negative effect brought by the relationship capital should not be neglected,including distorting the social equity,increasing social transaction cost,and weakening the public trust in government. It is a top priority to effectively evade its negative effect and bring into full play huge potential of the relationship capital.